2014
DOI: 10.1002/srin.201300423
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Secondary‐Dendrite Arm Spacing for Binary Alloys by Means of a Phase‐Field Model

Abstract: The mechanical properties and performance of metal materials depend on the intrinsic microstructures in these materials. In order to develop engineering materials as expected and to enable design with multifunctional materials, it is essential to predict the microstructural patterns, such as size, shape, and spacing of the dendritic structures observed in solidified metals. In materials science and related areas, the phase-field model is widely used as one of the powerful computational methods to simulate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…The concentrations in the solid indicate the presence of a microsegregation pattern. It should be observed that the phase-field calculations physically reproduces competitive growth of the columnar grains from the perturbed interface (Figure 9(a) and Figure 9(b)), the final arms spacing are independent of initial conditions, as discussed in [22]. On the other hand, spacing between columnar grains depends on the competitive growth of them during solidification.…”
Section: Results Of Coupling Between the Multiphase/multiscale Model mentioning
confidence: 55%
See 3 more Smart Citations
“…The concentrations in the solid indicate the presence of a microsegregation pattern. It should be observed that the phase-field calculations physically reproduces competitive growth of the columnar grains from the perturbed interface (Figure 9(a) and Figure 9(b)), the final arms spacing are independent of initial conditions, as discussed in [22]. On the other hand, spacing between columnar grains depends on the competitive growth of them during solidification.…”
Section: Results Of Coupling Between the Multiphase/multiscale Model mentioning
confidence: 55%
“…The copper concentration in solid is much less than that of copper in liquid. All the columnar dendritic grains are growing from left surface but the shapes of the arms are different from each other due to the imposed noise by Equation (22). In this simulation, a fine solid layer was added to left side of the domain boundaries.…”
Section: Phase-field Model Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(1), the phase-field equation. A usual expression for this noise, as indicated by Ferreira et al 13 , is…”
Section: Numerical Calculationsmentioning
confidence: 99%